Trueperella pyogenes Induced Cerebral Abscess in a West Highland White Terrier - Mustafa Usta (Sciendo, 2021)
Cerebral abscesses are occasionally seen in animals, however are rare in dogs. Among the pyogenic bacteria causing cerebral abscesses Trueperella pyogenes is relatively scarce. In this report, a case of T. pyogenes induced cerebral abscess in a West Highland White Terrier was presented with histopathological and bacteriological findings. Two foci of cerebral abscesses located at the level of the thalamus, and the frontal and temporal lobes were described on necropsy. Severe suppurative meningoencephalitis and ventriculitis were noted on microscopic view. T. pyogenes was isolated and identified in bacteriological investigation. This report states that T. pyogenes can be a causative agent of cerebral abscesses in dogs.